Disruptif diri pustakawan dalam menghadapi era revolusi industri 4.0 - Endang Fatmawati (UIN Sumatera Utara, 2018)
The library has undergone several evolutions in its development. Libraries will nevertheless continue to play a very important role as a source of lifelong knowledge. The impact of the 4.0 industry has integrated the advanced technology in a library. In addition, the user can work to analyze information independently. Today’s libraries are about engagement, collaboration, communication and partnerships. The librarian is there to solve the problem of the user in searching for information. Physical and digital technologies can be combined so as to provide complete information to make decisions and answer the needs of the user. The key to dealing with disruption is innovation and continuing to improve competence with technology.Keywords: disruptive 4.0, industrial revolution, innovation, collaboration.